Calulate the integral:
− ∞ ∫ ∞ cos ( x ) e − 2 x 2 d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is an implied use of Cauchy's integral theorem in your evaluation of the integral at the end. Essentially you're substituting u = x − i and using the known value of the integral of e − u 2 . But in fact this only works because of facts about contour integration; there are things to check. (Use a rectangular contour.)
Let I ( α ) = ∫ − ∞ ∞ c o s ( α x ) e − x 2 / 2 d x d α d I = − ∫ − ∞ ∞ x s i n ( α x ) e − x 2 / 2 d x
using integrating by parts : d α d I = [ s i n ( α x ) e − x 2 / 2 ] − ∞ ∞ − α ∫ − ∞ ∞ e − x 2 / 2 c o s ( α x ) d x d α d I = 0 − α I therefore, I ( α ) = ( c o n s t ) e − α 2 / 2 we know that I ( 0 ) = ∫ − ∞ ∞ e − x 2 / 2 d x = 2 π c o n s t = 2 π thus, ∫ − ∞ ∞ c o s ( x ) e − x 2 / 2 d x = 2 π / e = 1 . 5 2
Let start with infinite series!
Fisrt we have cos ( x ) = Σ n = 0 ∞ ( 2 n ) ! x 2 n ( − 1 ) n
So the integral becomes
∫ − ∞ ∞ cos ( x ) e − 2 x 2 d x = ∫ − ∞ ∞ ( Σ n = 0 ∞ ( 2 n ) ! x 2 n ( − 1 ) n ) e − 2 x 2 d x
Σ n = 0 ∞ ( ∫ − ∞ ∞ ( 2 n ) ! x 2 n ( − 1 ) n e − 2 x 2 d x )
∫ − ∞ ∞ ( 2 n ) ! x 2 n ( − 1 ) n e − 2 x 2 d x = ( 2 n ) ! ( − 1 ) n × ( 2 n − 1 ) ∫ − ∞ ∞ x 2 n − 3 e − 2 x 2 d x
Then ∫ − ∞ ∞ x 2 n e − 2 x 2 d x = 2 n n ! ( 2 n ) ! ∫ − ∞ ∞ e − 2 x 2 d x
Σ n = 0 ∞ ( ∫ − ∞ ∞ ( 2 n ) ! x 2 n ( − 1 ) n e − 2 x 2 d x ) = Σ n = 0 ∞ 2 n n ! ( − 1 ) n × ∫ − ∞ ∞ e − 2 x 2 d x
Σ n = 0 ∞ 2 n n ! ( − 1 ) n = e − 2 1
so the answer is
e − 2 1 × 2 π = e 2 π
Similar solution with @Humberto Bento 's
I = ∫ − ∞ ∞ cos x e − 2 x 2 d x = ∫ − ∞ ∞ ℜ ( e i x e − 2 x 2 ) d x = ℜ ( ∫ − ∞ ∞ e − 2 1 ( x 2 − 2 i x ) d x ) = ℜ ( ∫ − ∞ ∞ e − 2 1 ( ( x − i ) 2 + 1 ) d x ) = ℜ ( e 2 ∫ − ∞ ∞ e − u 2 d u ) = ℜ ( e 2 π ) = e 2 π ≈ 1 . 5 2 0 By Euler’s formula: e i θ = cos θ + i sin θ where ℜ ( z ) is the real part of z . Let u = 2 x − i ⟹ d u = 2 d x Note that ∫ − ∞ ∞ e − u 2 d u is Gaussian integral.
integral_(-infinity)^infinity (cos(x))/e^(x^2/2) dx = sqrt((2 pi)/e)~~1.5203469010662808056119401467549756270361074187790463375283638685267346239300583043148415372595655771
Yes, but how?
Problem Loading...
Note Loading...
Set Loading...
Ok, both solutions are very interesting. They are both nice and imaginative. Mine is a little less imaginative:
− ∞ ∫ + ∞ cos ( x ) e − 2 x 2 d x = − ∞ ∫ + ∞ ( cos ( x ) + i sin ( x ) ) e − 2 x 2 d x = − ∞ ∫ + ∞ e i x e − 2 x 2 d x = − ∞ ∫ + ∞ e − 2 x 2 + i x d x = − ∞ ∫ + ∞ e − 2 x 2 − 2 i x d x = − ∞ ∫ + ∞ e − 2 x 2 − 2 i x + i 2 e 2 i 2 d x = e − 2 1 − ∞ ∫ + ∞ e − 2 ( x − i ) 2 d x = e − 2 1 2 π = e 2 π
Using the gaussian result. Like both the other solutions, it's lacks somehow of a mathematical prove (the exchange between sum and integral for infinite limits of integration and the possibility of derivative under an integral with infinite range). The gaussian integral is not a shift on the real numbers. The prove is easy, though! Thanks to all. I've learned a lot!